Transportation Costs and Subsidy Distribution Model for Urban and Suburban Public Passenger Transport - Ševrović, Marko; Brčić, Davor; Kos, Goran (Promet - Traffic&Transportation, 2015)
Public transport (PT) subsidy provides the means to impose the optimal combination of fare and Level of Service (LoS) offered to passengers. In regions where one PT operator services multiple local communities on multiple lines it becomes hard to uniformly link the actual cost of a line and thus the LoS offered, to a particular local community. This leads to possible disproportions in the overall subsidy distribution that can result in being unfair to some local communities, mainly the ones that are sparsely populated or geographically isolated. In order to extricate this problem the appropriate level of PT subsidisation according to the average values in the European cities was investigated and the current subsidy policies in Croatia were investigated. Based on this research and the hypothesis that the offered LoS must be reflected in the subsidy amount a new subsidy distribution model was established that involves a series of analytical procedures and processes. This model introduces several factors used for the calculation of the actual share in costs. Thus, the amount of subsidies for individual lines in a region can be determined based on the actual service offered to the local community, The proposed model has been tested and successfully implemented in the Dubrovnik-Neretva County in the Republic of Croatia.